THE IMPACT OF THE FREE NUTRITIOUS MEALS PROGRAMME ON EDUCATORS AND STUDENTS AT SMPN 4 BANDAR LAMPUNG - Zakiya Rakha Fadhillah; Artika Permata; Bagus Kadek; Endi M Akbar (PT Wahana Global Education, 2025)
The Free Nutritious Meals Programme (MBG) is a government initiative aimed at improving students’ nutritional status while supporting the learning process. This study examines the impact of the MBG programme on educators’ performance and students’ learning conditions at SMPN 4 Bandar Lampung. A descriptive qualitative method was employed, with data collected through interviews with the deputy principal, teachers, students, and canteen managers. The findings show that the MBG programme positively affects students by improving focus, learning readiness, and efficiency in pocket money use. Students tend to be more energetic and prepared for learning after consuming the meals provided. For educators, the programme adds responsibilities related to distribution and supervision; however, these tasks do not disrupt teaching activities as they are managed during break times with a coordinated duty system. Overall, the MBG programme contributes positively to the school environment, although ongoing evaluation is needed to optimise its implementation.